How indoor environmental quality affects occupants’ cognitive functions: A systematic review - Wang, Chao; Zhang, Fan; Wang, Julian; Doyle, James K.; Hancock, Peter A.; Mak, Cheuk Ming; Liu, Shichao (Building and environment, 2021)
Cognitive functions refer to the set of brain-based skills to execute tasks of various difficulty levels. As people spend substantial time indoors, the indoor environmental quality (IEQ) influences occupants’ cognitive functions and consequently their learning and work performance. Previous studies have commonly examined the effects of IEQ on integrated learning or work performance, rather than specific cognitive skills. The present review decomposes IEQ into five factors—indoor air quality, the thermal environment, lighting, noise, and non-light visual factors. It divided cognition into five categories—attention, perception, memory, language function, and higher order cognitive skills—to better understand the relationship between IEQ and cognition. We conducted a detailed manual review of 66 focused studies and adopted co-occurrence analysis to generate landscapes of the associations between IEQ and cognition factors by analyzing keywords and abstracts of 8133 studies. Overall, results show that poor IEQ conditions are but not always associated with reduced cognition. However, the effects of a specific IEQ factor on different cognitive functions are quite distinct. Likewise, a specific cognitive function could be affected by different IEQ factors to varying degrees. Furthermore, the results suggest extensive inconsistencies in the relevant literature, especially regarding the effects of IAQ or thermal environment on cognition. Additionally, the keyword co-occurrence analysis identified more IEQ factors and cognitive functions emerging in the recent literature. Future studies are recommended to explore the factors causing the inconsistencies that we highlight here. [Display omitted] •Effects of IEQ factors on cognition are reviewed.•IEQ and cognition are but not always statistically associated.•Considerable conflicting results are identified among studies.•A specific IEQ factor may have varying effects on different cognitive functions.